On one method for the solution of an analog of the Cauchy problem for a polycaloric equation with singular Bessel operator - Karimov, Sh. T. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We study an analog of the Cauchy problem for an inhomogeneous singular polycaloric (polyparabolic) equation with Besseloperator. By using the Erd´elyi–Kober operator of the fractional order, we deduce an explicit formula for the solution of theformulated problem.